Innovative testing and measurement solutions for smart grid - Huang, Qi, 1976- (Wiley and Sons, Inc., 2015)
Focuses on sensor applications and smart meters in the newly developing interconnected smart grid- Focuses on sensor applications and smart meters in the newly developing interconnected smart grid- Presents the most updated technological developments in the measurement and testing of power systems within the smart grid environment- Reflects the modernization of electric utility power systems with the extensive use of computer, sensor, and data communications technologies, providing benefits to energy consumers and utility companies alike- The leading author heads a group of researchers focusing on the construction of smart grid and smart substation for Sichuan Power Grid, one of the largest in China's power system.